1967
DOI: 10.1002/cber.19671000604
|View full text |Cite
|
Sign up to set email alerts
|

1.3‐Dipolare Cycloadditionen, XXIX. Orientierungsphänomene bei der Anlagerung von Nitriliminen an α.β‐ungesättigte Carbonester, Vinyläther und Enamine

Abstract: A. Acrylsawe-methylester und seine DerivateSchon friihers) isolierten wir bei der Freisetzung des Diphenylnitrilimins (2) aus Benz-phenylhydrazid-chlorid (1) mit Triathylamin in Gegenwart von khylacrylat 85 % des kristallinen Addukts 3. Zur Prufung der Einheitlichkeit der Additionsrichtung lagerten wir 2 an iiberschussiges Methylacryrat in Benzol an. Der Schmp. des zu 100% anfallenden Rohaddukts war nur um 2" niedriger als der des analysenreinen 1.3-Diphenyl-A~-pyrazolin-carbonsaure-(5)-methylesters (4). Nach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…They used this approach to investigate cycloadditions of C-carbomethoxy-N-(4-substituted)phenylnitrilimines 2.10, aryl azides 2.11, and (4-substituted)benzonitrile oxides 2.12 with methyl propiolate 2.13 shown in Scheme 6. [32][33][34][35] The DW values correctly predict the preferred regiochemistry preference for all reactions considered. The authors also showed that DDW is proportional to the barrier heights and this correlation can be used to estimate product ratios between the regioisomers.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 95%
“…They used this approach to investigate cycloadditions of C-carbomethoxy-N-(4-substituted)phenylnitrilimines 2.10, aryl azides 2.11, and (4-substituted)benzonitrile oxides 2.12 with methyl propiolate 2.13 shown in Scheme 6. [32][33][34][35] The DW values correctly predict the preferred regiochemistry preference for all reactions considered. The authors also showed that DDW is proportional to the barrier heights and this correlation can be used to estimate product ratios between the regioisomers.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 95%
“…Vergleicht man die Regiochemie der 1-Addition an ethylenische 11) und acetylenische Carbonsaureester, dann fallt der hohere Anteil an 4-Carbonsaureestern bei den letzteren auf. Die ethylenischen Carbonsaureester reagieren urn eine Gronenordnung ra~cher'~).…”
Section: E Lo I C6h5 13unclassified
“…Hydrazonoyl halides have been widely employed for the synthesis of heterocyclic compounds [2][3][4]. 1,3,4-Thiadiazole derivatives have become useful in medicine, agriculture, and in many fields of technology [5].…”
Section: Introductionmentioning
confidence: 99%